Effect of Extraction Time And GC-MS Analysis of Fresh and Dry Frangipani Flower (Plumeria rubra L.) using Ultrasonic Assisted Extraction - Fatmawati, Sofia; Astari, Zhafirah; Bariroh, Tahyatul (Jurnal Ilmu Kesehatan, 2023)
Frangipani flower (Plumeria rubra) is one of the plants that has a role in perfume and aromatherapy technology which have essential compounds that are the main cause of fragrant smelling flowers. Optimization of extract production needs to be done to obtain a high content of active substances. Ultrasonic assisted extraction is a widely used method for extraction of active compounds in certain products due to shorter operating times. This study aims to determine the effect of variations in extraction time 30,45,60 minutes from fresh and dry frangipani flowers using ultrasonic methods on extract yield values ​​and chemical compositions using the GC-MS method. The results showed that the 60 minutes extraction produced the highest yield values, namely 5.11% for fresh yellow frangipani flower extract and 3.43% for dried yellow frangipani flower. The results of the chemical content study using GC-MS showed that the constituent compounds of fresh yellow frangipani flower essential oil consisted of fatty acids (6.59%), alkanoic acids (4.43%), triterpenoids (1.42%) and floral compound groups. Dry frangipani consists of alkanes (7.47%), alcohol (13.31%), fatty acids (1.00%).